2017
DOI: 10.3389/fmicb.2017.02359
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Shape Water Microbial Community Structure and Function in Shrimp Cultural Enclosure Ecosystems

Abstract: The effects of environmental factors on water microbial communities have been extensively studied, but little is known about the effects in shrimp cultural enclosure ecosystems. We analyzed 16S rRNA gene amplicons to determine the principal environmental factors that shape the structure and function of microbial communities in shrimp cultural enclosure ecosystems from Guangdong and Hainan provinces, in China. High quality sequences were clustered into operational taxonomic units (OTUs) at the 97% similarity le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(73 citation statements)
references
References 58 publications
6
67
0
Order By: Relevance
“…Fish silage is considered as a high-quality feed ingredient due to its balanced nutrition, palatability and bioactive substance. Unlike drastic conditions in these previous studies above (Cornejo-Granados et al, 2017;Hou et al, 2017),…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Fish silage is considered as a high-quality feed ingredient due to its balanced nutrition, palatability and bioactive substance. Unlike drastic conditions in these previous studies above (Cornejo-Granados et al, 2017;Hou et al, 2017),…”
Section: Discussionmentioning
confidence: 63%
“…Fish silage is considered as a high‐quality feed ingredient due to its balanced nutrition, palatability and bioactive substance. Unlike drastic conditions in these previous studies above (Cornejo‐Granados et al, ; Hou et al, ), replacement of fish meal by fish silage is insufficient to change metabolism functions of intestinal microbiota. This result indicated the limited impact of dietary fish silage on intestinal microbiota.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The influences of environmental factors on bacterial community compositions had been frequently observed in many environments, such as soils (Valentínvargas, Root, Neilson, Chorover, & Maier, ), lakes (Berdjeb, Ghiglione, Domaizon, & Jacquet, ), ocean (Dang et al, ) and aquaculture areas (Zhang, Wang, & Rong, ). The effects of environmental factors on water microbial communities have been investigated in shrimp cultural enclosure ecosystems and indicated that S, total phosphate, total nitrogen, T and pH were the most important factors shaping the bacterial communities (Hou et al, ). Large‐scale cultivation of seaweed increased DO and pH but decreased inorganic nutrients, which significantly altered the bacterial community compositions of both water and sediment in the cultivation zone (Xie et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore alga Fucus serratus consist of 25 genera, which represented 2 phyla (Ascomycota and Zygomycota) (Zuccaro et al, 2008). Beside technique approach, the habitat condition may influence the community structure of marine microorganism (Allison & Martiny, 2008;Hou et al, 2017).…”
Section: Composition Of Fungal Communities Associated With U Intestimentioning
confidence: 99%